Optimizing Health: Improving the Value of Healthcare Delivery - Porzsolt, Franz; Kaplan, Robert M.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
Are our patients getting what they want for their health care money? Should we change anything to give our patients more of what they want? Do we even know what they want? When service delivery, patient expectations, and the bottom line are in conflict, quality generally suffers. But such conflict can be minimized, say the editors of Optimizing Health. Answering elusive questions on how quality emerges in medical care, Franz Porzsolt and Robert Kaplan synthesize findings from closely interrelated aspects of clinical practice, clinical epidemiology, health economics, psychology, and ethics. The resulting systems perspective of this timely book merges thinking from clinical medicine and economics to form the hybrid term "CLINECS". The book challenges readers to rethink the standard criteria for assessing benefit to patients, and shows how evidence-based medicine can be incorporated into actual public health settings, clarifying key medical goals regarding patient autonomy. An international panel of experts offers practical, workable guidelines for: -Understanding the value of services from the patient’s point of view -Involving patients in medical decision-making -Avoiding overdiagnosis and overly aggressive treatment -Reconciling outcomes research and clinical research -Measuring patient quality of life—even for those who are cognitively impaired -Improving efficacy and effectiveness throughout the system Optimizing Health outlines an agenda of critical importance to health care professionals, researchers, and policymakers. This vision also makes it a bedrock graduate-level text for tomorrow’s clinicians and administrators. This is material that will be studied, discussed, debated, but most of all, benefited from.
Framework of CLINECS -- “CLINECS”: Strategy and Tactics to Provide Evidence of the Usefulness of Health Care Services from the Patient's Perspective (Value for Patients) -- Systems View of Health Care -- Ethics and Philosophy -- Seeking Justice in Health Care -- Evidence-Based Medicine and Ethics: Desired and Undesired Effects of Screening -- Paradoxes of Medical Progress: Abandoned Patients, Physicians, and Nurses -- Theory Behind the Bridge Principles -- Psychology -- How to Measure Quality of Life -- New Instrument to Describe Indicators of Well-Being in Old Old Patients with Severe Dementia: Vienna List -- Patient Empowerment: Increased Compliance or Total Transformation? -- Shared Decision Making in Medicine -- Clinical Practice -- Overdiagnosis and Pseudodisease: Too Much of a “Good Thing”? -- Palliative Medicine Today: Evidence and Culture -- Medical Geography–Who Gets the Goods? More May Not Be Better -- Cancer Survival in Europe and the United States -- Patient Safety: What Does It Mean in the United States? -- Increasing Safety by Implementing Optimized Team Interaction: Experience from the Aviation Industry -- Evidence-Based Information Technology: Concept for Rational Information Processing in the Health Care System -- Economically Oriented Analyses -- Cost-Effectiveness Analysis: Measuring the Value of Health Care Services -- Cost-Effectiveness of Lung Volume Reduction Surgery -- Health Economic Evaluation of Adjuvant Breast Cancer Treatment -- Aims and Value of Screening: Is Perceived Safety a Value for Which to Pay? -- Clinical Epidemiology -- Evidence-Based Health Care Seen From Four Points of View -- Efficacy, Effectiveness, and Efficiency of Diagnostic Technology -- Reduced Mammographic Screening May Explain Declines in Breast Carcinoma Among Older Women -- “Fading of Reported Effectiveness” Bias: Longitudinal Meta-Analysis of Randomized Controlled Trials -- Clinical Research and Outcomes Research: Common Criteria and Differences -- Are the Results of Randomized Trials Influenced by Preference Effects? Part I. Findings from a Systematic Review -- Are the Results of Randomized Trials Influenced by Preference Effects? Part II. Why Current Studies Often Fail to Answer this Question -- Conclusion and Outlook -- Suggested Changes in Practice, Research, and Systems: Clinical Economics Point of View.
Keywords: Public health; Health informatics; Public Health; Health Informatics